1999
DOI: 10.1046/j.0909-8836.1999.eos107610.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of potential tooth eruption molecules in the dental follicle of the mouse

Abstract: Tooth eruption requires alveolar bone resorption and the presence of the dental follicle, a loose connective tissue sac that surrounds each tooth. This bone resorption involves the follicle in that mononuclear cells enter the follicle to form osteoclasts which resorb bone to form the eruption pathway. In the rat first mandibular molar, probable eruption genes, CSF-1, c-fos, NFkappaB and MCP-1, are expressed maximally in the dental follicle at day 3 postnatally. This correlates with the time of peak influx of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Recognition that periodontal regeneration is possible has resulted in investigators' increased attempts to understand the cellular and molecular mechanisms and the factors that regulate formation of these tissues during development, maintenance, and regeneration. Clues to understanding the roles of specific factors in the regenerative process have come from developmental studies that examined the expression of genes/proteins during development of the periodontium (Wise et al, 1995(Wise et al, , 1999Takahashi and Ikeda, 1996;Aberg et al, 1997;D'Errico et al, 1997;Wise, 1998). We now show that inorganic pyrophosphate (PP i ) is one of the crucial factors that regulate both the initiation and maturation of cementum.…”
Section: Discussionmentioning
confidence: 96%
“…Recognition that periodontal regeneration is possible has resulted in investigators' increased attempts to understand the cellular and molecular mechanisms and the factors that regulate formation of these tissues during development, maintenance, and regeneration. Clues to understanding the roles of specific factors in the regenerative process have come from developmental studies that examined the expression of genes/proteins during development of the periodontium (Wise et al, 1995(Wise et al, , 1999Takahashi and Ikeda, 1996;Aberg et al, 1997;D'Errico et al, 1997;Wise, 1998). We now show that inorganic pyrophosphate (PP i ) is one of the crucial factors that regulate both the initiation and maturation of cementum.…”
Section: Discussionmentioning
confidence: 96%
“…Because resorption of alveolar bones is essential, previous studies about tooth eruption have focused on the tooth crown regions (2,30,31,43) . The expression of M‐CSF and c‐Fms, or other cytokines that may attract monocytes (precursors of osteoclasts) in the dental follicle, which is a loose connective tissue surrounding the developing tooth, has also been studied (44–46) . On the other hand, we emphasize that the inhibition of tooth eruption analyzed here is a part of the osteopetrotic condition and suggest that the number of TRAP + cells is a useful parameter.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted RT-PCR studies showed that colony-stimulating factor-one (CSF-1) and monocyte chemotactic protein-1 (MCP-1) were maximally expressed in the DF at day 3, the time of maximal influx of mononuclear cells (12,13). This correlation is strengthened by studies in mice in which the maximal influx of mononuclear cells is at day 5 (14) and the maximal expression of CSF-1 and MCP-1 is at day 5 in the mouse DF (15). In vitro, both MCP-1 and CSF-1 are secreted by the DF cells and are chemotactic for monocytes (13).…”
Section: Cellular and Molecular Events In The Df That Regulate Bone Rmentioning
confidence: 99%